Enriquecimento proteico do bagaço de malte por Rhizopus oligosporus CCT 4134 e adição em dietas de juvenis de tilápia do Nilo (Oreochromis niloticus) - Canedo, Marianny Silva (2015)
The majority of agroindustrial by-products are rich in low digestible fiber, and the bioconversion process for the production of microbial protein can be a practical and promising alternative to increase the protein content and nutritional value of substrate and food quality, turning these fibers into digestible components for the feeding of non-ruminant animals. Thus, this paper was aimed at protein enrichment of brewery spent grain by Rhizopus oligosporus CCT 4134 by solid state fermentation to be added in diets of juvenile Nile tilapia (Oreochromis niloticus). Solid state fermentation experiments were performed in order to determine the highest protein increment studying variables initial moisture (50, 60 and 70%) and supplemental nitrogen sources (ammonium sulfate, urea and sodium nitrate). To study the addition of fermented brewery spent grain in diets of Nile tilapia, 120 juveniles were used, divided into 24 boxes representing the six levels of addition (0, 2, 4, 6, 8 and 10%) of fermented brewery spent grain and four replications of each treatment. Fish were fed for 67 days between May and August 2015, the period where the water temperature was below the thermal comfort for the species. Solid state fermentation provided protein enrichment of brewery spent grain in about 2 and 4 times the content of crude and soluble protein, respectively, and is considered an alternative to use of industrial by-products to replace traditional ingredients in diets of juvenile Nile tilapia, because with the addition of fermented brewery spent grain, no significant difference in productive performance, hematological and biochemical parameters of juveniles Nile tilapia was found. Thus, the fermentation of brewery spent grain is a good alternative to be used as substrate for the cultivation of Rhizopus oligosporus and microbial protein production, allowing its use as a protein supplement in diets for juvenile Nile tilapia, with addition of up to 10 % without compromising growth performance and hematological parameters of the species.